A REEMERGÊNCIA DO SARAMPO NO BRASIL: FALHA DA COBERTURA VACINAL - Peixoto, Maria Eduarda Guedes; Neves, Ana Cláudia Ferreira; Aguiar, Marina Cavalcanti Rodrigues de; Fonseca, LetíciaSoares; Matioli, Luísa de Moura; Bhering, Carlos Alberto (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2022)
Measles is a highly contagious viral disease that can evolve with complications and deaths. The vaccination is the only effective measure to reduce or eliminate the disease. In 2018, in Brazil, measles resurged. The present study aims to analyze the incidence of measles in Brazil, between 2016 and 2020, associating its reemergence to the failure of vaccine coverage. An observational and cross-sectional study was carried out, based on data collection from epidemiological bulletins from the Health Surveillance Secretariat of the Ministry of Health and from the Hospital Information System in the Informatics Department of the Unified Health System. In 2016 and 2017 no measles cases have been confirmed in Brazil. In 2018, 10,330 cases and 12 deaths were confirmed; in 2019, 15,914 cases and 15 deaths; from january to october 2020, 8200 cases and 7 deaths. Between 2015 and 2019, less than 70% of brazilian municipalities reached the recommended vaccination coverage, which fell significantly in 2017. The measles virus arrived in Brazil due to the migratory movement, mainly from Venezuela to Amazonas, in 2018, spreading to the Southeast region. The resurgence of measles in Brazil occurred after the significant drop in vaccination coverage, a phenomenon also observed in the European Union and the United States. Because of this, it is necessary that the Ministry of Health reinforce its public policies regarding information about the disease and vaccination campaigns, to reduce the number of susceptible individuals, as well as viral circulation.